MODUL AJAR BUKU “CATATAN TARIM” ISMAEL AMIN KHOLILI DALAM MENGEMBANGKAN NILAI-NILAI PENDIDIKAN BERKARAKTER SISWA KELAS MENENGAH - kuswadi, annanda shofi sulthoni; Shohifur Rizal, Moh. Ahsan (Jurnal PENEROKA, 2024)
This research aims to analyze the teaching module entitled "Catatan Dari Tarim" by Ismael Amin Kholil in the context of developing character education values ??in middle class students. This research was carried out using the library research method which involved analysis of literature, references and relevant sources in order to understand the concept of character education and the values ??contained in the module. The research results show that the teaching module "Notes from Tarim" contains various character education values ??such as honesty, tolerance, brotherhood and so on. This teaching module also emphasizes spiritual values ??such as piety and sincerity in everyday life. This research provides additional insight into the potential use of literary works such as "Catatan Dari Tarim" as a relevant and useful source of character education. Apart from that, this research also highlights the importance of developing character education values ??as an integral part of education at the secondary level to help students become responsible and ethical individuals in their lives.